(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In a time of changing world, the process of globalization is exerting a powerful influence over all realms of life. Like other factors, globalization has had positive and negative effects on society. For instance, the sweeping changes brought by modernity and globalization led many people to view the representatives of other religions as hostile to the traditions of their religion. It would be more straightforward if every person tried to be tolerant to one another and showed his/her respect to the followers of other religions. Moreover, it would be better if big attention was paid to the upbringing of youth in a spirit of tolerance since they are considered as the future of society. As F. D. Roosevelt, the political leader, noted: “We cannot always build the future for our youth, but we can build our youth for the future. That’s why we have to bring the younger generation up in a spirit of tolerance in order to prevent the future problems”.